Dynamics of Physiological Poikilocytosis and Anisocytosis in Cholistani Cattle Blood - Rehman, Z. U.; Farooq, U.; Lashari, M. H.; Idris, M.; Asif, M.; Hameed, R.; Chaudhary, M. (Tropical Animal Science Journal, 2024)
The present study is the first account of physiological poikilocytosis and anisocytosis attained through stained peripheral blood smear in terms of prevalence, types, severity, and association with age, sex, and hemoglobin (Hb) levels in Cholistani cattle blood (n=64). The correlation of these red blood cells (RBC) forms has been made with certain RBC indices attained through a multi-species hematology analyzer. The total poikilocytes (24.7±0.2%) were significantly (p≤0.05) higher than the total anisocytes (8.4±0.1%) with echinocytes being the highest seen cells (5.4±0.5%). There was no statistical difference for poikilocytes and anisocytes between males and females. The spherocytes and schistocytes were significantly (p≤0.05) higher in young cattle as compared to adult cattle. All the animals in the study groups showed slight (13%-20%) to moderate (21%-30%) total poikilocytosis. Young (n=18; 28.1%) and females (n=7; 10.9%) revealed higher marked (˃30%) total poikilocytosis. The severity of total poikilocytosis did not significantly (p≤0.05) affect any of the RBC attributes. Normal cells were significantly higher (p≤0.05) in low Hb group being 68.5±1.5% as compared to 65.09±0.8% for high Hb group. The highest values were attained for the relation between total anisocytes and Hb, and between total anisocytes and Mean Corpuscular Hemoglobin Concentration (r-square=0.159; 15.9% probability). In conclusion, the blood of healthy Cholistani cattle presents physiological peculiarities in terms of the presence of various poikilocytes and anisocytes. Furthermore, the multi-species hematology analyzer failed to predict the level of poikilocytosis and anisocytosis in the present study, whereas the stained PBS provided reliable results.